2023
DOI: 10.3390/jcm12083046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pretreatment Systemic Inflammatory Markers on Treatment Persistence with Biologics and Conventional Systemic Therapy: A Retrospective Study of Patients with Psoriasis Vulgaris and Psoriatic Arthritis

Abstract: Systemic inflammation plays a central role in the pathophysiology of psoriasis. This study examined accessible systemic inflammatory markers in patients with psoriasis vulgaris and psoriatic arthritis. We aimed to evaluate their association with psoriasis severity, the presence of arthritis, and drug continuation rates. The findings revealed that neutrophil, monocyte, and platelet count, neutrophil/lymphocyte ratio, monocyte/lymphocyte ratio, systemic inflammation response index, systemic immune/inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…A major challenge and limitation is to find better predictors of treatment response to determine which patients are more likely to benefit from specific biologics. SII is positively correlated with PASI scores ( 30 – 32 ), and the correlation with treatment response ( 31 , 33 , 34 ) has been confirmed by some studies. In addition, correlations have been found between SII and metabolic syndrome ( 64 ), cardiovascular disease ( 65 ), and depression ( 66 ) in psoriasis comorbidities.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A major challenge and limitation is to find better predictors of treatment response to determine which patients are more likely to benefit from specific biologics. SII is positively correlated with PASI scores ( 30 – 32 ), and the correlation with treatment response ( 31 , 33 , 34 ) has been confirmed by some studies. In addition, correlations have been found between SII and metabolic syndrome ( 64 ), cardiovascular disease ( 65 ), and depression ( 66 ) in psoriasis comorbidities.…”
Section: Discussionmentioning
confidence: 56%
“…More recently, Sugimoto et al. also demonstrated a positive correlation between SII and PASI scores and found that patients with higher SII scores had lower persistence of treatment with conventional systemic medications ( 31 ). Dincer Rota et al.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic inflammatory cutaneous disorder which has been related to comorbidities such as psoriatic arthritis, diabetes, obesity, cardiovascular diseases and depression due to underlying systemic inflammation [ 1 ]. It has been suggested that proinflammatory cytokines, which have been implicated in the development of cutaneous findings such as tumor necrosis factor (TNF)-α, interleukin (IL)-17, IL-23, were increased in both skin and the circulation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory biomarkers, especially obtained from blood samples, may be easily performed and used in the follow-up of patients with psoriasis [ 5 ]. Various biomarkers such as neutrophil/lymphocytes ratio, platelet/lymphocytes ratio and systemic immune inflammation index have been proposed to be used to detect systemic inflammation in patients with psoriasis [ 1 , 5 ]. However, there is no consensus on the biomarkers that can be used to create an optimized treatment strategy in the management of psoriasis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation